Secondary Prevention after Myocardial Infarction: What to Do and Where to Do It - Tuka, Vladimír; Holub, Josef; Bělohlávek, Jan (Reviews in cardiovascular medicine, 2022)
Acute myocardial infarction is a manifestation of atherosclerosis which may be fatal. In-hospital and short-term mortality rates after an acute myocardial infarction have declined in the past few decades. However, although long-term mortality has decreased, it remains unacceptably high. This review paper summarises the non-pharmacological interventions (smoking cessation, physical activity, nutrition, and psychosocial intervention) and pharmacological approaches (antiplatelet and lipid-lowering therapy, renin-angiotensin-aldosterone system inhibitors, beta-blockers, and glucose-lowering drugs) to secondary prevention after a myocardial infarction. The provision of secondary prevention services is established through cardiac rehabilitation, which consists of several discussed components. Finally, we discuss the quality indicators for long-term care after an acute myocardial infarction.
Keywords: pharmacotherapy; secondary prevention; lifestyle; cardiovascular rehabilitation; myocardial infarction